Peer Review #3 of "Differential transcript profile of inhibitors with potential anti-venom role in the liver of juvenile and adult Bothrops jararaca snake (v0.1)" - Cícera M. Gomes; Karen de Morais-Zani; Stephen Lu; Diego S. Buarque; Regina Glória; Kathleen Fernandes Grego; Aparecida S. Tanaka; Anita Mitico; Tanaka-Azevedo Corresp; Anita Mitico Tanaka-Azevedo; Aparecida S. Tanaka (2017)
Background.Snakes belonging to the Bothrops genus are vastly distributed in Central and South America and are responsible for most cases of reported snake bites in Latin America.The clinical manifestations of the envenomation caused by this genus are due three major activities -proteolytic, hemorrhagic and coagulant -mediated by metalloproteinases, serine proteinases, phospholipases A 2 and other toxic compounds present in snake venom.Interestingly, it was observed that snakes are resistant to the toxic effects of its own and other snake's venoms.This natural immunity may occur due the absence of toxin target or the presence of molecules in the snake plasma able to neutralize such toxins.Methods.In order to identify anti-venom molecules, we construct a cDNA library from the liver of B. jararaca snakes.Moreover, we analyzed the expression profile of four molecules -the already known anti-hemorrhagic factor Bj46a, one gammaphospholipase A 2 inhibitor, one inter-alpha inhibitor and one C1 plasma protease inhibitorin the liver of juvenile and adult snakes by qPCR.Results.The results revealed a 30-fold increase of gamma-phospholipase A 2 inhibitor and a minor increase of the inter-alpha inhibitor (5-fold) and of the C1 inhibitor (3-fold) in adults.However, the Bj46a factor seems to be equally transcribed between adults and juveniles.Discussion.The results suggest the up-regulation of different inhibitors observed in the adult snakes might be a physiological adaptation to the recurrent contact with their own and even other snake's venoms throughout its lifespan.This is the first comparative analysis of ontogenetic variation of expression profiles of plasmatic proteins with potential anti-venom activities of